What attracts me or prevents me from mobile shopping? An adapted UTAUT2 model empirical research on behavioral intentions of aspirant young consumers in Pakistan. Issue 5 (30th September 2021) - Hanif, Muhammad Shehzad; Wang, Min; Mumtaz, Muhammad Usman; Ahmed, Zeeshan; Zaki, Waqas
Abstract : Purpose: Acceptance and use of mobile shopping as the preferred shopping medium is becoming the new normal today. The proliferation of mobile shopping practices follows unsteady growth patterns in different countries. Despite challenges of price, quality and privacy matters, young consumers still lead the race to engage in mobile shopping activity in developing countries. This research investigates the determinants that either support or hinder the mobile shopping intentions of aspirant young consumers in Pakistan. Design/methodology/approach: The present research applies a consumer-centric approach to the technology adoption framework to unearth the behavioral patterns of these young consumers in Pakistan. Employing the structural equation modeling technique, this research examines the significant effect of structural assurance, perceived risk, trust and various unified theory of acceptance and use of technology (UTAUT) model constructs on behavioral intention to engage in mobile shopping. Findings: This research examines the significant effect of structural assurance, perceived risk, trust and various UTAUT model constructs on behavioral intention to engage in mobile shopping. Results also demonstrate a significant moderating effect of structural assurance and prior shopping experience on the relationship between perceived risk, trust and mobile shopping intentions. Further, the mobile shopping patterns for the male and female segment indicate a significant difference for perceived risk, trust structural assurance and social influence. The research contributes to the growing body of knowledge which advocates the application of consumer-centric customized model approach to explore various factors that either facilitate or impede the adoption of mobile shopping in a developing economy. Research limitations/implications: The study validates the need to enforce structural assurance mechanism for facilitating mobile shopping in a developing country. It also offers practical implications for online businesses and marketers striving to attract and retain more mobile customers. Practical implications: The study offers practical implications for online businesses and marketers striving to attract and retain more mobile customers. Originality/value: This study offers fresh insights about driving elements and impediments of mobile shopping behavioral intentions. Structural assurance and prior shopping experience appear to influence the mobile shopping behavior through direct and indirect effect.